Surgical Robotics in Modern Oncology: Precision, Promise, and Pragmatism - Lamichhane, Nirmal (Nepalese Journal of Cancer, 2026)
The field of surgical oncology has undergonea profound transformation with the advent ofminimally invasive techniques, and more recently,robotic-assisted surgery. Building upon thefoundations of laparoscopy, robotic platforms suchas the da Vinci Surgical System have introducedenhanced dexterity, three-dimensional visualization,and improved ergonomics, redefining surgicalprecision in oncologic care¹.Robotic surgery has rapidly gained acceptanceacross multiple oncologic disciplines, particularly inurologic, gynecologic, and colorectal malignancies.Its technological advantages—including tremorfiltration, wristed instrumentation, and superiorvisualization—enable meticulous dissection inanatomically constrained regions such as the pelvisand mediastinum². These features are especiallyrelevant in cancer surgery, where achieving negativemargins and preserving critical structures areparamount.